Awareness of breast cancer and breast self-examination among nursing students - Uttam Chandani, Kanishka; Trivedi, Bhavi S.; Trivedi, Jaahnavee J.; Trivedi, Keval; Patel, Alpesh (International Journal Of Community Medicine And Public Health, 2020)
Background: The purpose of the study was to study awareness and knowledge amongst girls about breast self-examination and breast cancer. Methods: An educational interventional study was carried out among 150 students of V. S. Hospital, School of Nursing. Students were educated about prevalence and severity of breast cancer as well as early detection techniques in an interactive lecture. Pre- and post-tests were administered before and after session. Data was analysed by using Epi Info 3.5.3. Results: It was found that 91% subjects were aware of the term of breast self-examination (BSE). Post intervention, awareness increased by 100%. Half of the subjects believed that practice of breast self-examination should begin at the age of 20 years, poste intervention, awareness increased in 93%. Approximately one fourth of the students were aware of the ideal frequency of performing BSE, after the intervention, awareness level increased to 83%. Only 27% of subjects were aware of technique of BSE. Post the intervention, it was found that 87% became aware about the correct technique. There was improvement of 49% in knowledge about indicators of breast cancer. Conclusions: There was increase in awareness among girls about breast self-examination and breast cancer after intervention.